Plant-based pigments: Challenges and future perspectives for natural food colourants / Nurul Asyikin Md Zaki and Junaidah Jai - Md Zaki, Nurul Asyikin; Jai, Junaidah (Universiti Teknologi MARA, 2020)
Many synthetic food colourants have been developed to improve food products quality due to increasing demands. However, synthetic additives have been associated with numerous side effects and toxicity, allergic reactions, behavioural, and neurocognitive effects. Hence, consumer demands and their preferences for food colourants from natural origins have increased tremendously over the decades. With the growing interests for naturally derived and plant-based food ingredients to replace synthetic additives, many studies were done to provide safer and more effective food colourants. Among the highly explored plant-based pigments are anthocyanins, betacyanins, and carotenoids. Recently, there is also discovery on the newly found auronidins as potential pigment for future food application. This paper highlights on the features of plant-based pigments and its challenges, opportunities, and the way forward in food industry. Continuous research in this area is important for the development of more stable and intense pigments. Recent findings could be one of the ways to increase the stability of plant-based pigments to be applied in food industry